Two new species of eelpout genus Lycenchelys (Perciformes: Zoarcidae) from the Kuril-Kamchatka Trench, based on morphological and molecular evidence - Thiel, Ralf; Knebelsberger, Thomas; Chernova, Natalia; Eidus, Irina (Zootaxa, 2025)
Two new species of eelpout genus Lycenchelys Gill, 1884 are described based on eight specimens caught at a depth between 3517 and 3580 m at the western slope of the upper margin of the Kuril-Kamchatka Trench, relatively close to the Bussol Strait and Simushir Island in the center of the Kuril Islands chain. Lycenchelys delanglei sp. nov. differs from its congeners by the following combination of characters: vertebrae 28–29 + 91–93 = 120–121; interorbital and occipital pores absent; postorbital pores 4; suborbital pores 10–12; preoperculomandibular pores 4 + 5; gill rakers 11–16; dorsal-fin rays 114–117, 2–3 free pterygiophores at the beginning of dorsal fin; anal-fin rays 96–98; pelvic-fin rays 2; pectoral-fin rays 16–17, ray tips of the pectoral fin exserted, especially the middle and lower ones; lateral line absent; pyloric caeca not developed. Lycenchelys renatae sp. nov. differs from its congeners by the following combination of characters: vertebrae 26–27 + 99–103 = 125–130; interorbital pores 0–1; occipital pores absent; postorbital pores 1–4; suborbital pores 6–9; preoperculomandibular pores 3–4 + 5; gill rakers 13–15; dorsal-fin rays 115–122, 1–3 free pterygiophores at the beginning of dorsal fin; anal-fin rays 102–106; pelvic-fin rays two; pectoral-fin rays 16–17, ray tips of the pectoral fin exserted, the middle and lower ones more so than the upper ones; lateral line mediolateral, poorly developed; pyloric caeca not developed. For each of the two described new species four mitochondrial COI sequences were analysed and share the same haplotype within species. The obtained DNA barcodes allowed discrimination of L. delanglei sp. nov. and L. renatae sp. nov. from each other and exhibit a genetic distance of 2,61%. The closest match of L. delanglei sp. nov. with already published sequences was Lycenchelys lenzeni with a sequence similarity of 98.47%, whereas the closest match of L. renatae sp. nov. with already published sequences was Lycenchelys jordani with a similarity of 98.62%. A new analysis of radiographs of the type specimens confirmed that L. birsteini should be considered as synonym of L. plicifera, especially due to similar numbers of free pterygiophores at the beginning of dorsal fin.